2020
DOI: 10.1080/13501763.2020.1733636
|View full text |Cite
|
Sign up to set email alerts
|

The threat of social decline: income inequality and radical right support

Abstract: Income inequality and radical right parties have both been on the rise in Western democracies, yet few studies explore the linkages between the two -despite prominent arguments about voters feeling 'left behind'. We argue that rising inequality not only intensifies relative deprivation, but also signals a potential threat of social decline, as gaps in the social hierarchy widen. Hence, voters higher up in the social hierarchy may turn to the radical right to defend existing social boundaries. Using Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 49 publications
(89 reference statements)
3
92
0
Order By: Relevance
“…In particular, increasing inequality is shown to be a driving force of social polarisation and can hamper the development of togetherness (Uslaner, 2010; Uslaner and Brown, 2005). In this regard, our findings also link to the literature on populism which has recently shown that inequality affects support for populist parties (Engler and Weisstanner, 2020). Thus, perceived disadvantages are amplified by inequality making people more susceptible to populist actors.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, increasing inequality is shown to be a driving force of social polarisation and can hamper the development of togetherness (Uslaner, 2010; Uslaner and Brown, 2005). In this regard, our findings also link to the literature on populism which has recently shown that inequality affects support for populist parties (Engler and Weisstanner, 2020). Thus, perceived disadvantages are amplified by inequality making people more susceptible to populist actors.…”
Section: Discussionsupporting
confidence: 81%
“…Drawing on individual-level panel data, Kurer (2020) comes to a similar conclusion in that the relative decline in the social hierarchy makes (male) routine workers susceptible to the nativist platforms of PRRPs. This position is in line with Engler and Weisstanner (2021) who find that growing income inequality creates a fear of social decline among previously dominant political groups -individuals with high subjective social status and lower-middle incomes -, which have turned into an important electorate of PRRPs. What these studies suggest is that the threat of decline in social status, rather than actual outcomes of decline (e.g.…”
Section: Welfare-related Causes Of Prrps: Explaining the Rise Of The Radical Rightsupporting
confidence: 81%
“…It is no coincidence that this distinction between actual and potential decline features prominently on the research agenda about the consequences of economic changes for radical right party support (Gidron and Hall 2017;Kurer and Palier 2019;Engler and Weisstanner 2020;Kurer 2020), whereas actual job loss moves voters to the left (Wiertz and Rodon 2019). Our study contributes to this debate by showing that individuals whose job is at risk of being automated do not view a universal basic income as a viable remedy.…”
Section: Discussionmentioning
confidence: 75%